(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
In today’s digitally mediated communication landscape, subtitling has shifted from a peripheral linguistic transfer to a central practice of meaning-making that shapes comprehension, emotion, and engagement across online platforms. This study addresses the fragmentation of existing subtitling research by systematically reviewing recent scholarship on functional and pragmatic approaches to subtitling in digital media. Guided by the PRISMA protocol, the review identified, screened, and synthesized 10 peer-reviewed journal articles published between 2020 and 2025, retrieved from the Scopus database. Each study was analysed using thematic coding to capture recurrent concepts related to functional orientation, pragmatic strategy, audience reception, and platform affordances. The results reveal a paradigmatic shift in audiovisual translation: subtitles are now designed less for linguistic equivalence and more for communicative efficiency, emotional resonance, and cognitive accessibility. Five key themes emerged: reconfiguration of subtitling ecology, platform-specific adaptation, audience reception, automation and pragmatic adequacy, and pedagogical expansion, illustrating how subtitles serve as multimodal discourse tools within interactive digital ecosystems. The discussion highlights the novelty of integrating functionalist and pragmatic paradigms to reconceptualise subtitling as an audience-oriented discourse practice rather than a technical by-product. This review contributes to a more holistic theoretical understanding of subtitling while offering implications for translation pedagogy, digital media design, and cross-cultural communication. Future research is encouraged to explore comparative platform studies and AI-mediated subtitling to enhance cognitive and pragmatic effectiveness in rapidly evolving digital contexts.